Impact, scope of practice and competencies of Advanced Practice Nurses within APN-led models of care for young and middle-aged adult patients with multimorbidity and/or complex chronic conditions in hospital settings: a scoping review protocol - Reto W Kressig; Gabriele Bales; Wolfgang Hasemann; Hanna Mayer (BMJ Open, 2023)
Introduction The increase of young and middle-aged adult patients with multimorbid and/or complex chronic conditions has created new challenges for healthcare systems and services. Advanced Practice Nurses (APNs) play an essential role in treating these patients because of their expertise and advanced nursing skills. Little is known about competencies, scope of practice and impact of APNs within APN-led care models for young and middle-aged adult patients with multimorbidity and/or complex chronic conditions in hospital settings. The objective of this scoping review is to describe the impact, scope of practice and competencies of APNs within APN-led care models for young and middle-aged adult patients in hospital settings.Methods and analysis This scoping review will be conducted using the methodological framework proffered by Arksey and O'Malley, incorporating the methodological enhancement of Levac et al. It will comply with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) for Scoping Reviews’ guidelines of Tricco et al. Systematic research will be conducted in the databases MEDLINE (PubMed), CINAHL (EBSCO), EMBASE (Ovid), CENTRAL and PsycINFO (Ovid) using all recognised keywords, index terms and search strings. Grey literature will be scanned. Bibliography of all selected studies will be hand searched. Studies will be selected based on defined inclusion and exclusion criteria, screened by title and abstracts. Data from full-text articles meeting the inclusion criteria will be extracted independently by two authors. Disagreements in evaluation will be discussed and resolved by consensus. Results will be reported in the form of descriptive tables. Narrative summery is used to present the results of the review in the context of the study’s objectives and questions.Ethics and dissemination This scoping review does not require ethics approval. The review will be handed in as part of a doctoral thesis and published in a peer-reviewed journal.Trial registration number OSF 4PM38.